2001
DOI: 10.1097/00000478-200107000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathologic Analysis Enhances the Diagnosis and Management of Muir-Torre Syndrome and Gives Insight Into Its Underlying Molecular Pathogenesis

Abstract: The Muir-Torre syndrome (MTS) is an autosomal dominantly inherited disorder, characterized by visceral malignancies and sebaceous skin lesions. In a subset of MTS families the disease is due to an underlying DNA mismatch-repair defect. We have identified a MTS family whose spectrum of reported neoplasia included adenocarcinomas of numerous gastrointestinal sites, carcinomas of the endometrium, ovary and breast, papillary transitional cell carcinoma of the ureter, a range of cutaneous tumors, as well as keratoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…While there appears to be no increased risk of breast cancer in hereditary nonpolyposis colorectal cancer (HNPCC) 29,30 , we and many others have reported that a proportion of breast cancers arising in carriers of MMR gene mutations in the context of HNPCC exhibit molecular pathological evidence that the MMR gene dysfunction is associated with tumorigenesis of the breast 31,32 . MSI has been detected in a wide variety of human neoplasms associated with and without a family history of cancer and represents diagnostic criteria for mismatch repair deficiency 33,34 .…”
Section: Discussionmentioning
confidence: 94%
“…While there appears to be no increased risk of breast cancer in hereditary nonpolyposis colorectal cancer (HNPCC) 29,30 , we and many others have reported that a proportion of breast cancers arising in carriers of MMR gene mutations in the context of HNPCC exhibit molecular pathological evidence that the MMR gene dysfunction is associated with tumorigenesis of the breast 31,32 . MSI has been detected in a wide variety of human neoplasms associated with and without a family history of cancer and represents diagnostic criteria for mismatch repair deficiency 33,34 .…”
Section: Discussionmentioning
confidence: 94%
“…MSI testing was done on invasive tumor cells microdissected from 5-Am sections of paraffin-embedded archival tumor tissue stained with 1% methyl green. DNA extracted from histologically normal cells microdissected from colonic or lymph node tissue, or DNA extracted from peripheral blood lymphocytes, was used to control the assay as described previously (1,16,19). Ten microsatellite markers were assessed: 3 dinucleotide repeats (D5S346, D17S250, and D2S123) and 7 mononucleotide repeats (BAT25, BAT26, BAT40, MYB, TGFhRII, IGFIIR, and BAX).…”
Section: Methodsmentioning
confidence: 99%
“…For the purpose of this study, the degree of instability in each tumor was scored in two ways. The first used data from all 10 markers to categorize tumors as microsatellite stable ( 10 MS-Stable), low ( 10 MSI-Low), and high ( 10 MSI-High) when 0 to 1, 2 to 5, and 6 to 10 markers, respectively, were identified as unstable (1,16 (7). Assessment of MSI was not successful for 11 (10%) tumor samples due to technical reasons related to tumor DNA quality, leaving 107 tested tumors, which included 106 colorectal, and one stomach tumor (collected from a case where the colorectal cancer could not be located at the diagnostic laboratory).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the protein level, hMLH1/hMSH2 immunohistochemistry has a role in detecting MMR defects [51][52][53] , with data suggesting that the effectiveness of immunohistochemical screening of the MMR proteins would be similar to that of the more complex strateg y of microsatellite genotyping [54] . This technique can guide which gene to sequence and can help differentiating sporadic from hereditary mutations: hMSH2 loss is likely to be HNPCC, whereas hMLH1 loss could be HNPCC or sporadic CRC (MLH1 promoter methylation).…”
Section: Immunohistochemical Testing For Mmr Defectsmentioning
confidence: 99%